1999
DOI: 10.1038/sj.ejhg.5200271
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Ichthyosis: further narrowing, physical and expression mapping of the chromosome 2 candidate locus

Abstract: Lamellar ichthyosis (LI) is an autosomal recessive genodermatosis which has been shown to be both clinically and genetically heterogeneous. Keratinocyte transglutaminase (or transglutaminase 1: TGM1) has been demonstrated to be the disease-causing gene in some families, whilst in others, a second unidentified LI gene was mapped to chromosome 2q33-35 (ICR2B locus). In this study, we present a physical map that encompasses the ICR2B locus, including the mapping of new microsatellite markers. Based on this new ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Thus we propose that the desmosome is an important site for the initiation of CE assembly. Furthermore, these observations have important implications for the disease lamellar ichthyosis caused by lack of a functional TGase 1 enzyme (33,(47)(48)(49). If the initiation of CE assembly as envisaged above cannot occur, we should expect profound problems with formation of an effective barrier, as it is clear that the TGase 2 and 3 enzymes also expressed in terminally differentiating keratinocytes which do not bind to membranes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we propose that the desmosome is an important site for the initiation of CE assembly. Furthermore, these observations have important implications for the disease lamellar ichthyosis caused by lack of a functional TGase 1 enzyme (33,(47)(48)(49). If the initiation of CE assembly as envisaged above cannot occur, we should expect profound problems with formation of an effective barrier, as it is clear that the TGase 2 and 3 enzymes also expressed in terminally differentiating keratinocytes which do not bind to membranes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is of critical importance in skin barrier function in particular since mutations in its gene resulting in loss of activity cause the devastating life-threatening disease lamellar ichthyosis (47)(48)(49). Most of the TGase 1 enzyme resides on membranes through N-myristoyl and S-myristoyl or S-palmitoyl linkages (30 -32), although minor amounts dissociate to reside in the cytosol (46).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is conceivable that mutations that affect directly those enzyme systems responsible for these post-synthetic modifications should result in a TGase 1 enzyme of greatly reduced specific activity or potential for proteolytic processing, with consequences of LI disease. In this regard, it is noteworthy that cases of CRI have been identified that do not involve mutations in the TGM1 gene (11)(12)(13). Further work must be done now to explore whether mutations in these ancillary gene systems, directly or indirectly affecting the TGase 1 enzyme, are the cause of CRI or LI disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical findings include palmar-plantar hyperkeratosis, eclabium, ectropion, scarring alopecia, and diminished skin barrier function. Recent studies have revealed marked biochemical (7,8) as well as genetic variations in CRI patients as follows: to date, in certain families, linkage has been described to chromosome regions 14q11 (9, 10), 2q33-35 (11), or to neither (11)(12)(13). However, all cases of the large brown plate scaling phenotype have been linked to 14q11, and several different mutations in the TGM1 gene located at this site have been identified (10, 11, 14 -15).…”
Section: Congenital Recessive Ichthyoses (Cri)mentioning
confidence: 99%
“…We and others have shown that mutations in the gene for transglutaminase-1 (TGM1) cause the vast majority of cases of classic LI (Russell et al 1995;Huber et al 1995). An exception is a group of seven families from Northern Africa, where the phenotype co-segregates with markers on chromosome 2, although no gene has yet been identified (Parmentier et al 1996(Parmentier et al , 1999.…”
Section: Introductionmentioning
confidence: 97%